2012
DOI: 10.1590/s0102-09352012000300027
|View full text |Cite
|
Sign up to set email alerts
|

Influência do período de armazenamento na qualidade do ovo integral pasteurizado refrigerado

Abstract: RESUMOAvaliaram-se o pH e a qualidade microbiológica de ovos integrais pasteurizados refrigerados obtidos de dois tipos de matéria-prima: o ovo in natura (comercial ) e o ovo galado (ovo fértil). Os tratamentos foram dispostos no delineamento inteiramente ao acaso, em parcelas subdivididas, sendo na parcela dois tipos de ovos integrais pasteurizados, o comercial e o galado, e na subparcela quatro períodos de estocagem sob temperatura de refrigeração, um, sete, 14 e 21 dias. Não foi observada a presença de Salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
14

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 4 publications
1
11
0
14
Order By: Relevance
“…Taham & Oliveira (2011), in a study on Salmonella spp., also observed the absence of microorganisms in 67% of the samples of eggs sold in Brasília (Federal District). These data corroborate those obtained by Rego et al (2012), who Freitas et al (2011) reported a weight loss in the eggs that were stored without any temperature control. According to these authors, the eggs' weight loss was due to the reduction of water in the albumen since the ratio decreased as a function of the storage time, which was significantly greater in the eggs that were kept at room temperature.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Taham & Oliveira (2011), in a study on Salmonella spp., also observed the absence of microorganisms in 67% of the samples of eggs sold in Brasília (Federal District). These data corroborate those obtained by Rego et al (2012), who Freitas et al (2011) reported a weight loss in the eggs that were stored without any temperature control. According to these authors, the eggs' weight loss was due to the reduction of water in the albumen since the ratio decreased as a function of the storage time, which was significantly greater in the eggs that were kept at room temperature.…”
Section: Resultssupporting
confidence: 91%
“…The total thermotolerant coliforms count were 4 NMP.g -1 , but the presence of E. coli was not confirmed. Rego et al (2012), in a study on commercial pasteurized eggs, found a total coliforms ranging from <0.3-NMP.g -1 to 110 NMP.g -1 . However, there were no coliforms during the storage period at 45 °C in commercial pasteurized whole eggs.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The importance of egg quality for human nutrition is well known (Rêgo et al, ). However, after laying, eggs undergo several metabolic processes (oxidation) and their quality decreases (Wardy, Torrico, No, Prinyawiwatkul, & Saalia, ), resulting in limited shelf life of 21 days.…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, é fundamental que esse alimento tenha boa condição no armazenamento para que mantenha suas qualidades nutricionais até chegar ao consumidor. (REGO et al, 2012) Durante o armazenamento dos ovos, o pH do albúmen aumenta, e esta velocidade varia de acordo a temperatura, sendo que, este aumento deve-se à perda de dióxido de carbono através dos poros presentes da casca, o que pode ocasionar a deterioração do albúmen (XAVIER et al, 2008). A avaliação de qualidade do ovo foi realizada no laboratório de nutrição animal localizado no IF Baiano Campus Santa Inês, onde foram avaliados os seguintes parâmetros: Peso, comprimento e largura do ovo, gravidade especifica, altura do albúmen, unidade Haugh (UH), peso da gema, peso da casca, peso do albúmen, relação gema albúmen, espessura da casca, cor da gema.…”
unclassified